2013
DOI: 10.1136/jclinpath-2012-201217
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of visual assessments of proliferation indices in gastroenteropancreatic neuroendocrine tumours

Abstract: Manual tally counts of 2000 cells exhibited similar levels of accuracy to the gold standard, especially at low PIs. Eyeball estimates were significantly less accurate than the gold standard. This suggests that tumour grades may be misclassified by eyeballing and that formal tally counting of positive cells produces more reliable results. Further studies are needed to identify accurate clinically appropriate ways of calculating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…However, multi-institutional studies showed that formal counting was more reproducible than estimation in breast cancer [53,75]. Similar observation were made in NEN: results of eyeballed estimation differed from results of counting [20,21,25] and were irreproducible [25], but some investigators showed that estimation was not as bad [27,28]. Pathologists in general overestimate the Ki67 LI during eye-balled estimation in comparison to counting technique [25,27].…”
Section: Toward Optimal Methods Of Ki67 LI Assessmentsupporting
confidence: 52%
See 1 more Smart Citation
“…However, multi-institutional studies showed that formal counting was more reproducible than estimation in breast cancer [53,75]. Similar observation were made in NEN: results of eyeballed estimation differed from results of counting [20,21,25] and were irreproducible [25], but some investigators showed that estimation was not as bad [27,28]. Pathologists in general overestimate the Ki67 LI during eye-balled estimation in comparison to counting technique [25,27].…”
Section: Toward Optimal Methods Of Ki67 LI Assessmentsupporting
confidence: 52%
“…Analytical validity is a sine qua non condition for any tumour biomarker which is intended to be used in clinical practice and to influence management of the patients [18]. Selected aspects of analytical validity of Ki67 LI in NEN were previously studied [19,20,21,22,23,24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The mitotic index should be calculated by counting at least 500 and preferably 2000 cells; studies have noted that ''eyeballing'' and estimating the percentage is quite inaccurate, particularly at lower levels of activity, and therefore a strict count (either manual or by image analysis methods) is recommended. 47,48 There is general agreement that the count should be performed in the area of highest mitotic activity (hotspots). However, concern remains about what level of staining constitutes a true positive nuclear staining; Young et al 48 noted specifically that ''cells were considered positive if they showed any evidence of taking up stain.''…”
Section: Grading and Staging Of Netsmentioning
confidence: 99%
“…47,48 There is general agreement that the count should be performed in the area of highest mitotic activity (hotspots). However, concern remains about what level of staining constitutes a true positive nuclear staining; Young et al 48 noted specifically that ''cells were considered positive if they showed any evidence of taking up stain.'' While this appears logical, validation of this approach is not available.…”
Section: Grading and Staging Of Netsmentioning
confidence: 99%
“…Nevertheless, two operators only were enrolled to count, and they did not even analyzed live and dead cells separately. Recently, Young et al [44] improved the statistics by asking four operators to count, but they did not report results regarding either inter-observer variability or dead cells. In conclusion, no statistical analyses have been reported in literature to extensively compare the gold standard method with an approach based on a labelled mosaic.…”
Section: Introductionmentioning
confidence: 99%